Time-Variant Simulation of Multi-Material Thermal Pultrusion - Chen, X. (2015)
Pultrusion being the viable and economical process for producing constant cross-section composite products, many variants of it are being tried out. This paper embarks on the pultrusion with multi-materials; typically of polymer foam/glass fibre reinforced polymer (GFRP) sandwich panels. Unlike conventional composites pultrusion, this process with more than two material phases, one of them dry, poses a challenge in simulating the thermal co-curing within the die. In this paper, the formulation and development of three-dimensional, finite element/nodal control volume (FE/NCV) approach for such multi-material pultrusion is presented. The numerical features for handling the dry-wet material interfaces, material shrinkage, variations in pull speed and die heating, and foam-to-skin thickness ratio are discussed. Implementation of the FE/NCV procedure and its application in analyzing pultrusion of polymer foam/GFRP sandwich panels with multi-heater environment are presented.